Therapeutic efficacy of tylvalosin combined with Poria cocos polysaccharides against porcine reproductive and respiratory syndrome - Shi, Hong; Luo, Wentao; Wang, Shuaiyang; Dai, Jun; Chen, Cuilan; Li, Shuo; Liu, Jie; Zhang, Weiyuan; Huang, Qi; Zhou, Rui (Frontiers in Veterinary Science, 2023)
Porcine reproductive and respiratory syndrome (PRRS) is one of the most economically important infectious diseases of pigs worldwide. Vaccination and various management measures have been implemented to control PRRS. However, due to high genetic diversity and insufficient understanding of the pathogenesis and immunological mechanisms, PRRS is still a challenge to the pig industry. Therefore, it is important to develop novel strategies to combat PRRS virus (PRRSV) infection. In this study, our data show that tylvalosin, a third-generation animal-specific macrolide, could inhibit PRRSV replication in MARC-145 cells, and suppress the PRRSV-induced NF-κB activation and cytokines expression. The pig infection experiment further demonstrated that tylvalosin could significantly reduce the virus loads in serum and tissues, and alleviate lung lesions of pigs infected with highly pathogenic PRRSV strains. The fever and loss of daily gain (LoDG) of the pigs were decreased as well. Considering the feature of immune suppression of PRRSV, a combination of tylvalosin with the immunopotentiator Poria cocos polysaccharides (PCP) was developed. Pig experiment showed this combination had a better therapeutic efficacy against PRRSV infection than tylvalosin and PCP alone in attenuating lung lesions, alleviating fever, and suppressing cytokines production. This study suggests that tylvalosin has significant antiviral and anti-inflammatory effects against PRRSV infection, and the combination of tylvalosin and PCP provides a promising strategy for PRRS treatment.